2010
DOI: 10.1029/2009jd013486
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of individual submicrometer aerosol particles collected in Incheon, Korea, by quantitative transmission electron microscopy energy‐dispersive X‐ray spectrometry

Abstract: [1] For the last decade the Monte Carlo calculation method has been proven to be an excellent tool for accurately simulating electron-solid interactions in atmospheric individual particles of micrometer size. Although it was designed for application to scanning electron microscopy, in the present study it is demonstrated that the Monte Carlo calculation can also be applied in a quantitative single particle analysis using transmission electron microscopy (TEM) with an ultrathin window energy-dispersive X-ray (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 69 publications
(88 reference statements)
3
40
0
Order By: Relevance
“…A fraction of the particulate chlorides in sea salts is converted into gas-phase compounds (e.g., HCl and ClNO 2 ), with most of the remaining chlorides completely encased within a large quantity of inorganic elements (as shown in Fig. 2(b)) (e.g., Mg and S at Cape Grim , K, Ca, and S in Incheon (Geng et al, 2010), Mg, K, Ca, and S in Antarctica (Hara et al, 2005), and Mg, N, and S in Houston, Macao, and Hong Kong (Laskin et al, 2002;Li et al, 2010Li et al, , 2016a). Amorphous sodium chloride particles were found to be completely bound with sodium nitrates and sodium sulfates in coastal Hong Kong (Li et al, 2016a).…”
Section: Mixing Of Chlorides In Sea Saltsmentioning
confidence: 99%
See 1 more Smart Citation
“…A fraction of the particulate chlorides in sea salts is converted into gas-phase compounds (e.g., HCl and ClNO 2 ), with most of the remaining chlorides completely encased within a large quantity of inorganic elements (as shown in Fig. 2(b)) (e.g., Mg and S at Cape Grim , K, Ca, and S in Incheon (Geng et al, 2010), Mg, K, Ca, and S in Antarctica (Hara et al, 2005), and Mg, N, and S in Houston, Macao, and Hong Kong (Laskin et al, 2002;Li et al, 2010Li et al, , 2016a). Amorphous sodium chloride particles were found to be completely bound with sodium nitrates and sodium sulfates in coastal Hong Kong (Li et al, 2016a).…”
Section: Mixing Of Chlorides In Sea Saltsmentioning
confidence: 99%
“…Electron microscopy and single-particle mass spectrometry have indicated that potassium chlorides in biomass burning smoke mix with soot and organics, and some even acquire an organic surface coating (Silva et al, 1999;Li et al, 2003b). In urban areas, field studies have detected plentiful submicron metal chloride containing particles, which are typically mixed with carbonaceous materials in combustion emissions (Moffet et al, 2008b;Li et al, 2009;Geng et al, 2010;Hu et al, 2015). Additionally, in long-range transport dust plumes over the Pacific, Sullivan et al (2007b) observed that a large amount of secondary particulate chlorides (produced from gas-phase HCl) was internally mixed with dust particles.…”
Section: Introductionmentioning
confidence: 99%
“…Morphology and EDS data suggest that the particles were regarded as mixtures of semi and/or less volatile organic species and ammonium sulfate/bisulfate (see Fig. 9c) (Geng et al, 2010). Approximately 12 over 95 particles were identified to be of this type in the photochemical event in urban Gwangju together with industrial Yeosu sites.…”
Section: 3 Morphological and Elemental Analysis Of Ufpsmentioning
confidence: 99%
“…UFP number concentrations, gaseous pollutants, and meteorological data, averaged by the time of day, obtained in urban Gwangju , 2010, 2011, and 2012), coastal Taean (2008), and industrial Yeosu (2008 sites in Korea by continuously measuring particle number size distribution N (13-615 nm) are summarized in Table 1. The variation of UFP number concentrations in three different sampling sites: Gwangju, Taean, and Yeosu, and seasonal and long-term variations in urban Gwangju are described as follows.…”
Section: Variation Of Ufp Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation